POMEGRANATE JUICE AMELIORATES ATENOLOL TOXIC EFFECTS ON EMBRYO DEVELOPMENT - S. Zafar; Asmatullah1and C. Ara (Journal of Animal and Plant Sciences, 2020)
Hypertension is an increasing issue experienced by females during pregnancy. Gestational hypertension is treated by many antihypertensive drugs including methyldopa, beta blockers, and calcium channel blockers. Atenolol is usually the drug of choice by obstetricians among beta blockers. Objective of this study was to find the fetotoxic effects of Atenolol in albino mice and protective potential of pomegranate juice against potential atenolol toxicity. Embryotoxic effect of atenolol was determined in pregnant mice, force fed orally through gavage three different atenolol concentrations (3.30µg/g, 2.50µg/g, 1.65µg/g body weight of treated mice, respectively) from 6th -12th day of gestation. Other three groups were made for antidote study and 50% diluted pomegranate juice was provided to each group along with above mentioned atenolol concentrations as an antidote. During osteogenesis, fetuses in atenolol exposure groups have varying degree of incomplete ossification in dose dependent way. Histological analysis had also shown teratogenic potential of atenolol in developing mice embryos. The present study revealed that administration of atenolol during organo-genetic period upset prenatal development in mice fetuses. To minimize the toxic effects of drug, pomegranate juice was provided to experimental mice. Positive outcomes represented that pomegranate juice has protective potential against Atenolol induced fetotoxicity.
Keywords: Atenolol; Fetotoxity; Hypertension; Ameliorative; Pomegranate